Impedimetric Evaluation of Hybrid Cationic Porphyrin/Quantum Dot Multilayer Assemblies: A Biocompatible Interface for Calf Thymus Dna Immobilization - Aguirre-Quintana, M; Aguirre-Quintana, M; Ruiz-Leon, D; Ruiz-Leon, D; Garcia-Sanhueza, C; Garcia-Sanhueza, C; Navarro-Gajardo, F; Navarro-Gajardo, F (Springer New York LLC, 2017)
In this work, a cationic porphyrin, ascribed as [Ttolyl(P-(C6H5)3)4]4+, where Ttolyl = 5,10,15,20 tetrakistolylporphyrin, was electrostatically assembled with CdTe quantum dots capped with glutathione (GSH) of diameter ~3.28 nm via a layer-by-layer methodology. This multilayer assembly was evaluated as a biocompatible interface with synergic effects for calf thymus double-stranded DNA (CT DNA) immobilization, considering that the hybrid assembly contains a cationic porphyrin with a high binding constant for CT DNA, and quantum dots with polypeptide as a capping agent. The multilayer assembly, ascribed as ITO/{[Ttolyl(P-(C6H5)3)4]4+/CdTe}n (n = 1–5), was characterized by UV-Vis spectroscopy, cyclic voltammetry, and electrochemical impedance spectroscopy (EIS). The last technique was explored in order to check the adsorption of CT DNA onto the multilayer porphyrin/quantum dot assembly. The difference in electron transfer resistance (ΔRct) obtained after CT DNA incubations showed the best result for a specific multilayer assembly, n = 3. {[Ttolyl(P-(C6H5)3)4]4+/CdTe}3 showed a good correlation of ΔRct with the logarithmic concentration of CT DNA, in the range 1.0 × 10−10 to 1.0 × 10−6 M with a limit of detection (LOD) of 1.5 × 10−12 M. Conversely, when the {[Ttolyl(P-(C6H5)3)4]4+/CdTe}3 system was incubated with calf thymus single-stranded DNA and salmon testes DNA, no significant difference in ΔRct was observed. We conclude that the newly described {[Ttolyl(P-(C6H5)3)4]4+/CdTe}n system is a choice method for the impedimetric determination of CT DNA. © 2016, Springer-Verlag Berlin Heidelberg.